A technical note on the effect of log length on the drying of Eucalyptus urophylla. Issue 4 (2nd October 2021) - da Abreu Neto, R.; Monteiro, T. C.; Lima, J. T.; da Silva, J. R. M.
ABSTRACT: This study aimed to evaluate the drying rate of Eucalyptus urophylla hybrid logs of different lengths used for carbonisation. Six seven-year-old trees of two clones (VM4 and MN463) were harvested from experimental plots located in the region of Paraopeba, Minas Gerais, Brazil. Specimens were cut into four different lengths so that the ratios between cross-sectional area and curved-surface area were 1:1, 1:2, 1:5 and 1:10. Samples were then air-dried in an open shed for 170 days. Drying rates were calculated for different periods during air-drying. The fastest drying rates were observed during the first 28 days during the removal of free water. In general, the free-water drying rate was 5.7 times higher than that for bound water and 2.5 times higher than total drying rate. At the end of drying, the shortest drying rate occurred in shorter samples, being 3.2 times faster than the longest logs, regardless of the genetic material analysed. These findings are important for charcoal-producing industries, potentially helping that sector improve drying efficiency and produce higher-quality charcoal.